(untitled) (Journal of Economic Research & Business Administration, 2017)
Formation of market economy in Kazakhstan could not but put a number of new problems, the most important of which is the problem of аnti- crisis management, before society. It is explained, first of all, by the fact that one of factors of modern Kazakhstan economy is insolvency of most the enterprises. Many enterprises owing to the reasons which roots go to the system of socialist managing developing decades did not manage to adapt to new economic conditions so far that was promoted by the general economic instability, inconsistency in implementation of market reforms, adverse investment climate, inefficient tax policy and other macroeconomic factors. At the same time the understanding that, despite all difficulties in development of real production sector, a lot of things depend on the enterprises, on their owners and managers, on their activity directed to achievement of stability grows in society. For efficiency of development of industrial development enterprises within formation of technological potential, basing on local scientific and innovative potential, on full-scale adaptation (on all levels, including innovative) the imported technologies is essentially important.